A case of refractory urethritis with repeated doctor shopping. Issue 2 (22nd January 2022) - Maeda, Koki; Shigemura, Katsumi; Yang, Yong‐Ming; Nakano, Yuzo; Arakawa, Soichi; Fujisawa, Masato
Abstract : Introduction: In the field of sexually transmitted diseases, resistance and diversification of causative organisms are becoming a problem. We report a case in which the course of the disease was complicated by doctor shopping. Case presentation: A man in his 40s visited his local doctor for painful urination and cloudy urine. Due to the lack of improvement in symptoms after antibiotic treatment, he self‐selected to visit six hospitals in just five months. He visited our clinic only a few times and then stopped coming. Conclusion: Doctor shopping, as well as self‐diagnosis and self‐treatment, will continue to increase. Patient education is important, but medical professionals also need to be aware of the possibility of doctor shopping when treating patients.